Method for producing clean fuel by utilizing sludge based on piezoelectric catalysis assisted hydrothermal carbonization
By using bismuth tungstate piezoelectric catalyst for piezoelectric catalytic pretreatment during hydrothermal carbonization of sludge, the extracellular polymer and cell structure of sludge is destroyed, and the problem of high nitrogen content in hydrothermal carbonization of sludge is solved. The goal of producing low-nitrogen clean fuels and environmental protection has been achieved.
Patent Information
- Application Number
- CN202411527692.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The hydrothermal carbon produced by hydrothermal carbonization is high, resulting in fuel-type NOx generated during combustion, affecting the operation of the equipment and causing environmental pollution.
The piezoelectric catalysis-based method is used to pretreat the sludge with bismuth tungstate piezoelectric catalyst to destroy its extracellular polymer and cellular structure, thereby reducing the nitrogen content in hydrothermal carbon.
It effectively reduces the nitrogen content in hydrothermal carbon, reduces nitrogen oxide emissions during solid fuel combustion, improves energy efficiency, reduces operating costs, and reduces environmental pollution.
Smart Images

Figure CN119391467A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the resource utilization of sludge in the field of environmental engineering, and in particular to a method for producing clean fuel by utilizing sludge based on piezoelectric catalysis-assisted hydrothermal carbonization. Background Art
[0002] With the rapid development of industrialization and urbanization, the current municipal sludge treatment faces huge challenges. Sludge is a byproduct of sewage treatment. Due to its large amount and strong pollution, how to effectively deal with it has become an international issue. Sewage sludge contains a large amount of organic matter and microorganisms. Proper treatment of it can effectively utilize resources and reduce environmental pollution, which is of great significance.
[0003] At present, the common disposal methods of sludge are mainly landfill and incineration, which not only occupy a large amount of land resources but also cause the problem of low energy utilization. Hydrothermal carbonization is a technical method that uses water as a solvent and reaction medium, and dehydrates and decarboxylates sludge at 180℃-250℃ and autogenous pressure to obtain carbon as the main body. This technology can directly treat sludge with high water content to achieve sludge reduction; and can use high temperature to achieve biological sterilization and material decomposition, reducing subsequent pollution to the environment and achieving sludge harmlessness; at the same time, sludge hydrothermal carbonization can produce hydrothermal carbon, densify the energy of sludge, and realize the resource utilization of sludge. However, the hydrothermal carbon produced by sludge hydrothermal carbonization currently has a high nitrogen content, which is mainly due to the inability to destroy the extracellular polymers (EPS) of the sludge during the hydrothermal carbonization process, which limits its possibility of being directly used as a substitute for fossil fuels or mixed with fossil fuels. In order to deal with this problem, sludge is often pretreated in research, such as adding chemical reagents or using advanced oxidation methods to treat sludge, which deeply destroys the floccules, EPS and even cell structures of sludge to release sludge organic matter and nitrogen precursors. However, in order to achieve better results, large doses of chemicals are generally added, which limits their commercial application.
[0004] Considering that sludge will experience vibration processes such as transportation, filtration, filter pressing and dehydration during disposal, if these vibration energies can be effectively utilized and strengthened to achieve initial destruction of sludge, this will be beneficial to energy conservation and the subsequent production of low-nitrogen hydrothermal carbon. Piezoelectric catalysis happens to be a technology that relies on the absorption of vibration energy to produce free radicals and remove organic matter. This technology has gradually attracted people's attention due to its high energy-to-electricity conversion efficiency and convenient energy utilization. It is reported that the electromechanical energy conversion efficiency based on the piezoelectric effect can reach 78%, which is much higher than the 20% energy conversion efficiency of photovoltaics. At present, commonly used piezoelectric catalysts include Bi2WO6, BiTiO3 and TiO2. Among them, Bi2WO6 has low cost and large spontaneous polarization (Ps≈50μC cm -2 ) and good piezoelectric response have gradually attracted people's attention. However, the low separation efficiency of electron-hole pairs of Bi2WO6 affects its catalytic efficiency and further use.
[0005] Constructing heterojunctions on piezoelectric catalysts to form new piezoelectric catalytic materials is an effective method to improve the efficiency of electron-hole separation. At present, the heterojunction construction method based on transition metal sulfides, such as CoS x ,CdS,MoS2,SnS2,and CuS have gradually attracted people's attention and use due to their excellent catalytic performance and special band gap, and have great prospects for utilization. Among them, SnS2 has attracted much attention in pollutant removal and chemical catalysis due to its high conductivity and stability.
[0006] Based on the above background, the current technology of producing clean fuel by hydrothermal carbonization of sludge has the following problems and challenges:
[0007] (1) The hydrothermal carbon fuel produced by sludge hydrothermal carbonization has a high nitrogen content and exists in a relatively stable form. These nitrogen-containing substances generate fuel-type NO during the combustion process. x , affecting equipment operation and causing environmental pollution;
[0008] (2) The nitrogen-containing substances in sludge are mainly proteins, most of which are present in sludge EPS. The stubbornness of the EPS structure is the key to the above problems. The strong hydrogen bonding in EPS makes it impossible to effectively destroy and release proteins during the hydrothermal process, which further affects the decomposition of these substances under dehydration, decarboxylation and other reactions, ultimately resulting in a low degree of carbonization and a high nitrogen content.
[0009] Therefore, there is an urgent need to find a method to destroy sludge extracellular polymers with low energy consumption and low dosage, release organic matter and nitrogen-containing precursors, and produce low-nitrogen hydrothermal carbon clean fuel. Summary of the invention
[0010] Purpose of the invention: In view of the shortcomings of the above-mentioned existing sludge hydrothermal carbonization technology, the present invention proposes a method for producing clean fuel by utilizing sludge based on piezoelectric catalysis-assisted hydrothermal carbonization, and applies piezoelectric catalysis technology to the hydrothermal carbonization process of sludge, thereby achieving the destruction of sludge extracellular polymers and cell structure, reducing the nitrogen content in hydrothermal charcoal, and reducing nitrogen oxide emissions during solid fuel combustion; the present invention realizes the resource utilization of sludge and the production of low-nitrogen clean fuel, and has the advantages of improving energy efficiency, reducing operating costs and reducing environmental pollution.
[0011] Technical solution: In order to achieve the above-mentioned purpose, the present invention uses a method for producing clean fuel by piezoelectric catalysis-assisted hydrothermal carbonization of sludge, comprising the following steps:
[0012] (1) Mixing sludge with deionized water, adding the prepared bismuth tungstate piezoelectric catalyst according to the dry weight ratio of the sludge, and then placing it in an ultrasonic machine for piezoelectric catalytic pretreatment; the preparation process of the bismuth tungstate piezoelectric catalyst is as follows:
[0013] (1.1) using a hydrothermal synthesis method, dissolving bismuth nitrate pentahydrate in glacial acetic acid, adding sodium tungstate dihydrate solution, reacting at high temperature, washing and drying, and obtaining bismuth tungstate nanosheets;
[0014] (1.2) dissolving tin tetrachloride pentahydrate and thioacetamide in deionized water, reacting at high temperature, washing and drying to obtain tin sulfide;
[0015] (1.3) Dispersing bismuth tungstate and tin sulfide nanosheets in anhydrous ethanol, heating and evaporating the ethanol after magnetic stirring to obtain a heterojunction piezoelectric catalyst;
[0016] (2) The pretreated sludge is placed in a hydrothermal reactor and subjected to hydrothermal carbonization reaction at 180°C to 240°C for several hours. After cooling to room temperature, solid-liquid separation is performed and the solid phase is collected to obtain clean hydrothermal carbon.
[0017] In step (1), the sludge is mixed with deionized water, and the prepared piezoelectric catalyst is added at 10% of the dry weight of the sludge, and then placed in an ultrasonic machine for piezoelectric catalytic pretreatment for 3 to 6 hours.
[0018] Step (1.1), using a hydrothermal synthesis method, dissolving bismuth nitrate pentahydrate in glacial acetic acid; adding sodium tungstate dihydrate solution, and transferring to an autoclave to react at high temperature for several hours, washing the white product with anhydrous ethanol and deionized water, and drying at medium temperature to obtain bismuth tungstate nanosheets.
[0019] In step (1.1), the hydrothermal reaction temperature is 180°C and the drying temperature is 60°C.
[0020] In step (1.1), the volume of glacial acetic acid is 15 ml, the volume of sodium tungstate dihydrate solution is 25 ml, the volume ratio of the two is 3:5, and the concentration of bismuth nitrate pentahydrate glacial acetic acid solution is The concentration of sodium tungstate dihydrate solution is 0.04 mol / L.
[0021] In step (1.2), the molar ratio of tin tetrachloride pentahydrate to thioacetamide is 1:2, and the volume of deionized water is 40 ml.
[0022] In step (1.2), tin tetrachloride pentahydrate and thioacetamide are dissolved in deionized water and reacted at high temperature for several hours; the light yellow product is washed with anhydrous ethanol and deionized water, and dried to obtain tin sulfide.
[0023] In step (1.3), the evaporation temperature is 70° C., and the mass ratio of bismuth tungstate to tin sulfide is 20:1.
[0024] In step (2), the nitrogen removal rate formula of hydrothermal carbon is:
[0025]
[0026] In step (2), the pretreated sludge is placed in a hydrothermal reactor and reacted at 180°C to 240°C for several hours. After cooling to room temperature, a suction filtration device is used to separate the solid and liquid, and the solid phase is collected to obtain clean hydrothermal charcoal.
[0027] In step (1), the ratio of sludge to deionized water is 1:1 (g:ml); the processing power of the ultrasonic machine is 180W, and the pretreatment time is 3 / 6 hours.
[0028] In step (2), the hydrothermal reaction temperature is 190°C and the drying temperature is 60°C.
[0029] Working principle: The present invention is based on a piezoelectric catalytically assisted hydrothermal carbonization method for producing low-nitrogen clean hydrothermal carbon. A piezoelectric catalyst with a strong piezoelectric effect is prepared by adopting a hydrothermal synthesis method and a heterostructure construction. The method comprises mixing the sludge with deionized water, adding a piezoelectric catalyst for piezoelectric catalytic pretreatment; then subjecting the pretreated sludge to a hydrothermal carbonization reaction at 180°C to 240°C, and performing solid-liquid separation after the reaction to obtain clean hydrothermal carbon. The piezoelectric catalyst adopts a Bi2WO6@SnS2 heterojunction structure, that is, in the core working principle of the present invention, Bi2WO6@SnS2 is used as a piezoelectric catalyst, which produces ·OH and ·O under the action of piezoelectric vibration. 2-Free radicals. These free radicals effectively destroy the extracellular polymers (EPS) and cell wall structure of the sludge, thereby releasing a large amount of nitrogen-containing substances. In the process of further depolymerization of the released nitrogen-containing substances, especially proteins, are decomposed into low-molecular organic matter, such as soluble proteins and amino acids, under the high temperature environment of hydrothermal carbonization. This decomposition not only increases the content of ammonia nitrogen and total nitrogen in the liquid phase, but also inhibits the Maillard reaction by reducing the precursors of the Maillard reaction in the sludge, thereby reducing the generation of nitrogen-containing heterocyclic compounds and reducing the nitrogen sequestration in the hydrothermal carbon.
[0030] The present invention adopts the prepared heterojunction bismuth tungstate piezoelectric catalyst and puts it into an ultrasonic machine to pre-treat the sludge under piezoelectric vibration. On the one hand, by adjusting the structure of the catalyst, the piezoelectric effect of the piezoelectric catalyst is improved, and the production of high-quality hydrothermal carbon is achieved. On the other hand, the sludge is treated by hydrothermal carbonization, and the sludge is reduced in one step while also being recycled.
[0031] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0032] (1) The present invention uses hazardous waste - sludge as raw material, and prepares a new type of low-nitrogen hydrothermal carbon through hydrothermal carbonization technology, achieving efficient and clean conversion of solid waste. This method not only helps to reduce the environmental burden caused by solid waste landfill and incineration, but also opens up a new path for solid waste resource utilization.
[0033] (2) The present invention applies piezoelectric catalytic technology to the hydrothermal carbonization process of sludge for the first time, thereby destroying the extracellular polymers and cell structure of the sludge, reducing the nitrogen content in the hydrothermal carbon, and reducing nitrogen oxide emissions during the combustion of solid fuels. This has important environmental significance for controlling air pollution, especially reducing the formation of urban haze and acid rain.
[0034] (3) In the hydrothermal carbonization process of the present invention, the extracellular polymers and cell structures in the pretreated sludge are destroyed, making it easier to remove water, thereby significantly reducing energy consumption in the dehydration stage of the hydrothermal carbonization. This improvement improves the energy efficiency of the entire production process and reduces operating costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 A schematic diagram of the method for producing clean fuel by using sludge based on piezoelectric catalysis-assisted hydrothermal carbonization according to the present invention;
[0036] Figure 2 The infrared spectra of the hydrothermal carbon prepared under different conditions of the present invention;
[0037] Figure 3The peak intensity diagram of the pyrolysis products and the change diagram of the nitrogen-containing substance content of the hydrothermal carbon produced under different piezoelectric catalytic pretreatment conditions under 240°C hydrothermal carbonization of the present invention;
[0038] Figure 4 It is a paradigm diagram under different conditions of the present invention;
[0039] Figure 5 It is a graph of hydrothermal charcoal yield under different conditions of the present invention;
[0040] Figure 6 The SEM and TEM images of the piezoelectric catalyst synthesized by the present invention;
[0041] Figure 7 The XRD characterization diagram of the piezoelectric catalyst synthesized by the present invention;
[0042] Figure 8 This is the XPS fine map of the piezoelectric catalyst synthesized by the present invention;
[0043] Fig. 9 This is the piezoelectric loop diagram of the piezoelectric catalyst synthesized in the present invention. DETAILED DESCRIPTION
[0044] like Figure 1 As shown, the present invention first prepares a bismuth tungstate piezoelectric catalyst. The preparation method of the bismuth tungstate piezoelectric catalyst for constructing a heterojunction in the embodiment includes the following steps:
[0045] Step (1): Using a hydrothermal synthesis method, 0.9701 g of bismuth nitrate pentahydrate was dissolved in 15 ml of glacial acetic acid. Then 25 ml of 0.04 mol / L Na2WO4·2H2O solution was added and transferred to a 50 ml Teflon-lined stainless steel autoclave. After reacting at 180 degrees Celsius for 24 hours, the white product was washed three times with anhydrous ethanol and deionized water, and dried at a medium temperature of 60 degrees Celsius for 10 hours to obtain Bi2WO6 nanosheets.
[0046] Step (2): 2.1 g of tin tetrachloride pentahydrate and 0.9 g of thioacetamide were dissolved in 40 ml of deionized water. Then, the solution was transferred to a 50 ml Teflon-lined stainless steel autoclave maintained at 190 degrees Celsius for reaction for 13 hours. Finally, the pale yellow product was purified by washing with anhydrous ethanol and deionized water, and the SnS2 sample was obtained after drying at 60 degrees Celsius for 12 hours.
[0047] Step (3): 2 g Bi2WO6 and 20 mg SnS2 nanosheets were dispersed in 20 ml of sewage ethanol and then magnetically stirred for 3 h. Finally, the suspension was heated to 70 °C and the ethanol was evaporated for 12 h to obtain a heterojunction piezoelectric catalyst.
[0048] like Figure 1 As described in the following section, the method for producing clean fuel by using sludge based on piezoelectric catalysis-assisted hydrothermal carbonization in an embodiment of the present invention includes the following steps:
[0049] Step 1: Take 30 grams of sludge and place it in 30 ml of water, add a catalyst according to 10% of the dry weight of the sludge, and then put it into a 180W ultrasonic machine for piezoelectric catalytic pretreatment. The treatment time is 3 hours or 6 hours respectively.
[0050] Step 2: After the reaction is completed, place it in a hydrothermal reactor and react at a temperature of 180-240 degrees Celsius for 1 hour, then cool to room temperature. Use suction filtration to separate the solid and liquid, collect the hydrothermal liquid, and at the same time, place the hydrothermal charcoal in an oven at 60 degrees Celsius to dry for 12 hours, and grind and collect.
[0051] Among them, the nitrogen removal rate formula of hydrothermal carbon is:
[0052]
[0053] Example 1
[0054] Pretreatment time: 3 hours, hydrothermal carbonization temperature: 180°C
[0055] Pretreatment: The sludge was mixed with deionized water at a ratio of 1:1 (g:ml), and the synthesized Bi2WO6@SnS2 piezoelectric catalyst was added at 10% of the dry weight of the sludge. The mixture was placed in an ultrasonic machine with a treatment power of 180W and a pretreatment time of 3 hours.
[0056] Hydrothermal carbonization: The pretreated sludge is placed in a hydrothermal reactor and reacted at 180°C for 1 hour. After the reaction is completed, it is cooled to room temperature, and the solid-liquid separation is performed using a suction filtration device, and the solid phase is collected to obtain clean hydrothermal carbon.
[0057] Results: The nitrogen removal efficiency of the obtained hydrothermal carbon was 51.06%.
[0058] Example 2
[0059] Pretreatment time: 3 hours, hydrothermal carbonization temperature: 240°C
[0060] Pretreatment: Same as Example 1, the pretreatment time is 3 hours.
[0061] Hydrothermal carbonization: The pretreated sludge was placed in a hydrothermal reactor and reacted at 240° C. for 1 hour. The remaining steps were the same as in Example 1.
[0062] Results: The nitrogen removal efficiency of the obtained hydrothermal carbon was 61.47%.
[0063] Example 3
[0064] Pretreatment time: 6 hours, hydrothermal carbonization temperature: 180°C
[0065] Pretreatment: Same as Example 1, the pretreatment time is 6 hours.
[0066] Hydrothermal carbonization: The pretreated sludge was placed in a hydrothermal reactor and reacted at 180° C. for 1 hour. The remaining steps were the same as in Example 1.
[0067] Results: The nitrogen removal efficiency of the obtained hydrothermal carbon was 56.03%.
[0068] Example 4
[0069] Pretreatment time: 6 hours, hydrothermal carbonization temperature: 240°C
[0070] Pretreatment: Same as Example 1, the pretreatment time is 6 hours.
[0071] Hydrothermal carbonization: The pretreated sludge was placed in a hydrothermal reactor and reacted at 240° C. for 1 hour. The remaining steps were the same as in Example 1.
[0072] Results: The nitrogen removal efficiency of the obtained hydrothermal carbon was 71.16%.
[0073] Comparative Example 1
[0074] Without pretreatment, hydrothermal carbonization temperature: 180℃
[0075] Hydrothermal carbonization: Put the sludge directly into the hydrothermal reactor and react at 180°C for 1 hour. After the reaction is completed, cool it naturally to room temperature, use suction filtration equipment to separate the solid and liquid, collect the solid phase, and obtain hydrothermal carbon.
[0076] Results: The nitrogen removal efficiency of the obtained hydrothermal carbon was 26.24%.
[0077] Comparative Example 2
[0078] Without pretreatment, hydrothermal carbonization temperature: 240℃
[0079] Hydrothermal carbonization: Same as Comparative Example 1, the hydrothermal carbonization temperature was 240°C.
[0080] Results: The nitrogen removal efficiency of the obtained hydrothermal carbon was 43.97%.
[0081] Comparative Example 3
[0082] Pretreatment time: 3 hours, hydrothermal carbonization temperature: 180°C, catalyst: Bi2WO6
[0083] Pretreatment: Mix the sludge with deionized water at a ratio of 1:1 (g:ml), add Bi2WO6 catalyst at 10% of the dry weight of the sludge. Put the mixture into an ultrasonic machine with a treatment power of 180W and a pretreatment time of 3 hours.
[0084] Hydrothermal carbonization: The pretreated sludge was placed in a hydrothermal reactor and reacted at 180° C. for 1 hour. The remaining steps were the same as in Example 1.
[0085] Results: The nitrogen removal efficiency of the obtained hydrothermal carbon was 43.74%.
[0086] Comparative Example 4
[0087] Pretreatment time: 3 hours, hydrothermal carbonization temperature: 240°C, catalyst: Bi2WO6
[0088] Pretreatment: Same as Comparative Example 3, the pretreatment time is 3 hours.
[0089] Hydrothermal carbonization: The pretreated sludge was placed in a hydrothermal reactor and reacted at 240° C. for 1 hour. The remaining steps were the same as in Example 1.
[0090] Results: The nitrogen removal efficiency of the obtained hydrothermal carbon was 56.97%.
[0091] Comparative Example 5
[0092] Pretreatment time: 6 hours, hydrothermal carbonization temperature: 180°C, catalyst: Bi2WO6
[0093] Pretreatment: Same as Comparative Example 3, the pretreatment time is 6 hours.
[0094] Hydrothermal carbonization: The pretreated sludge was placed in a hydrothermal reactor and reacted at 180° C. for 1 hour. The remaining steps were the same as in Example 1.
[0095] Results: The nitrogen removal efficiency of the obtained hydrothermal carbon was 51.06%.
[0096] Comparative Example 6
[0097] Pretreatment time: 6 hours, hydrothermal carbonization temperature: 240°C, catalyst: Bi2WO6
[0098] Pretreatment: Same as Comparative Example 3, the pretreatment time is 6 hours.
[0099] Hydrothermal carbonization: The pretreated sludge was placed in a hydrothermal reactor and reacted at 240° C. for 1 hour. The remaining steps were the same as in Example 1.
[0100] The nitrogen removal rates of the hydrothermal carbon produced by the piezoelectric catalytic assisted hydrothermal carbonization of sludge according to the present invention and the nitrogen removal rates of the hydrothermal carbon without piezoelectric catalytic pretreatment are shown in Table 1.
[0101] Table 1
[0102]
[0103]
[0104] As can be seen from Table 1, the nitrogen removal rate of the hydrothermal carbon produced by the present invention using sludge based on piezoelectric catalysis-assisted hydrothermal carbonization is 51.06-71.16%, which can effectively produce low-nitrogen hydrothermal carbon.
Claims
1. A method for producing clean fuel using sludge based on piezoelectric catalysis-assisted hydrothermal carbonization, characterized in that: The following steps are involved: (1) Mixing sludge with deionized water, adding the prepared bismuth tungstate piezoelectric catalyst according to the dry weight ratio of the sludge, and then placing it in an ultrasonic machine for piezoelectric catalytic pretreatment; the preparation process of the bismuth tungstate piezoelectric catalyst is as follows: (1.1) using a hydrothermal synthesis method, dissolving bismuth nitrate pentahydrate in glacial acetic acid, adding sodium tungstate dihydrate solution, reacting at high temperature, washing and drying, and obtaining bismuth tungstate nanosheets; (1.2) dissolving tin tetrachloride pentahydrate and thioacetamide in deionized water, reacting at high temperature, washing and drying to obtain tin sulfide; (1.3) Dispersing bismuth tungstate and tin sulfide nanosheets in anhydrous ethanol, heating and evaporating the ethanol after magnetic stirring to obtain a heterojunction piezoelectric catalyst; (2) The pretreated sludge is placed in a hydrothermal reactor and subjected to hydrothermal carbonization reaction at 180°C to 240°C for several hours. After cooling to room temperature, solid-liquid separation is performed and the solid phase is collected to obtain clean hydrothermal carbon.
2. The method for producing clean fuel by using sludge based on piezoelectric catalysis-assisted hydrothermal carbonization according to claim 1, characterized in that: In step (1), the sludge is mixed with deionized water, and the prepared piezoelectric catalyst is added at 10% of the dry weight of the sludge, and then placed in an ultrasonic machine for piezoelectric catalytic pretreatment for 3 to 6 hours.
3. The method for producing clean fuel by using sludge based on piezoelectric catalysis-assisted hydrothermal carbonization according to claim 1, characterized in that: Step (1.1), using a hydrothermal synthesis method, dissolving bismuth nitrate pentahydrate in glacial acetic acid; adding sodium tungstate dihydrate solution, and transferring to an autoclave to react at high temperature for several hours, washing the white product with anhydrous ethanol and deionized water, and drying at medium temperature to obtain bismuth tungstate nanosheets.
4. The method for producing clean fuel by using sludge based on piezoelectric catalysis-assisted hydrothermal carbonization according to claim 1, characterized in that: In step (1.1), the hydrothermal reaction temperature is 180°C and the drying temperature is 60°C.
5. The method for producing clean fuel by using sludge based on piezoelectric catalysis-assisted hydrothermal carbonization according to claim 1, characterized in that: In step (1.1), the volume of glacial acetic acid is 15 ml, the volume of sodium tungstate dihydrate solution is 25 ml, and the concentration of bismuth nitrate pentahydrate glacial acetic acid solution is The concentration of sodium tungstate dihydrate solution is 0.04 mol / L.
6. The method for producing clean fuel by using sludge based on piezoelectric catalysis-assisted hydrothermal carbonization according to claim 1, characterized in that: In step (1.2), the molar ratio of tin tetrachloride pentahydrate to thioacetamide is 1:
2.
7. The method for producing clean fuel by using sludge based on piezoelectric catalysis-assisted hydrothermal carbonization according to claim 1, characterized in that: In step (1.2), tin tetrachloride pentahydrate and thioacetamide are dissolved in deionized water and reacted at high temperature for several hours; the light yellow product is washed with anhydrous ethanol and deionized water, and dried to obtain tin sulfide.
8. The method for producing clean fuel by using sludge based on piezoelectric catalysis-assisted hydrothermal carbonization according to claim 1, characterized in that: In step (1.3), the evaporation temperature is 70° C., and the mass ratio of bismuth tungstate to tin sulfide is 20:
1.
9. The method for producing clean fuel by using sludge based on piezoelectric catalysis-assisted hydrothermal carbonization according to claim 1, characterized in that: In step (2), the nitrogen removal rate formula of hydrothermal carbon is:
10. The method for producing clean fuel by using sludge based on piezoelectric catalysis-assisted hydrothermal carbonization according to claim 1, characterized in that: In step (2), the pretreated sludge is placed in a hydrothermal reactor and reacted at 180°C to 240°C for several hours. After cooling to room temperature, a suction filtration device is used to separate the solid and liquid, and the solid phase is collected to obtain clean hydrothermal charcoal.
Citation Information
Patent Citations
Heterostructured composite material formed by Bi2WO6 and SnS2, and preparation method thereof
CN110449167A
Composite piezoelectric catalytic material and preparation method and sludge dewatering application thereof
CN111068659A
Sludge dewatering method based on ultrasonic and hydrothermal carbonization
CN115072962A
A method forfabrication of direct z-scheme photocatalyst for water purification
IN201811033393A
Application of metal sulfide piezoelectric material in piezoelectric catalytic reduction of co2
US20240343669A1